Korelasi Tingkat Kecemasan dan Kualitas Tidur pada Lansia Hipertensi di Puskesmas Purwosari Kota Surakarta - Nur Lailli Ramadhani; Supratman Supratman (Jurnal Skala Kesehatan, 2026)
Hypertension, commonly known as the â€œsilent killerâ€ can induce anxiety in sufferers due to the need for long-term treatment. High levels of anxiety will impact the decline in sleep quality, which disrupts blood pressure stability and increases the risk of hypertension recurrence. This study examines the correlation between anxiety and sleep quality in elderly hypertensive patients at Purwosari Health Center, Surakarta. This research employs a quantitative approach with a cross-sectional correlational design, using the Geriatric Anxiety Scale (GAS) questionnaire to assess anxiety and the Sleep Quality Scale (SQS) to measure sleep quality. The study involved 159 respondents within the service area. A significant correlation exists between anxiety and sleep quality among hypertensive patients in the working area Purwosari Health Center, Surakarta City. The correlation test between anxiety and sleep quality yielded a significant value of p = 0.000 (P < 0.01). The Chi-Square analysis reveals a significant link between anxiety and sleep quality (p = 0.001, Hâ‚€ rejected, Hâ‚ accepted). Of the 80 respondents with mild anxiety, 54 (67.5%) had good sleep quality; whereas of the 79 respondents with moderate anxiety, 52 (65.8%) experienced poor sleep quality. Conclusion: The heavier the anxiety level, the worse the sleep quality, thus requiring appropriate interventions to reduce anxiety in elderly hypertension patients.